Chimeric peptide nanorods for plasma membrane and nuclear targeted photosensitizer delivery and enhanced photodynamic therapy. (September 2019) - Cheng, Hong; Yuan, Ping; Fan, Guiling; Zhao, Linping; Zheng, Rongrong; Yang, Bin; Qiu, Xiaozhong; Yu, Xiyong; Li, Shiying; Zhang, Xianzheng
Abstract: Tumor therapeutic efficiency is largely determined by the delivery efficacy of therapeutic agent to its final target, especially for photodynamic therapy (PDT). Although plasma membrane or nuclear targeted photosensitizer delivery is considered to be a promising strategy for enhanced photodynamic tumor therapy, they have been confronted with some difficulties and challenges. In this work, the self-delivery chimeric peptide nanorods (denoted as pnPNP) are developed for plasma membrane and nucleus dual-targeted photosensitizer delivery to achieve the synergetic in situ PDT. In vitro investigations demonstrate that the dual-targeting capability benefits the efficient subcellular localization of pnPNP in plasma membrane and nucleus. Plasma membrane targeted PDT of pnPNP could improve the membrane permeability to enhance the cellular uptake, even trigger the membrane disruption and cause cell necrosis directly. Upon light irradiation, the internalized pnPNP could effectively disrupt lysosomal structures and realize the nuclear permeation for supplementary nuclear targeted PDT. Abundant experiments verify that the plasma membrane and nucleus dual-targeted PDT exhibit a far better anti-tumor effect than the single nuclear targeted PDT. This synergistic subcellular dual-targeting strategy maximizes the PDT therapeutic efficacy, which also provides a new insight for the development of advanced drug delivery systems.